BrainScripts for sales success : 21 hidden principles of consumer psychology for winning new customers - Whitman, Drew Eric (McGraw-Hill Education, 2015)
Why do some salespeople close deals like crazy, and others usually only get doors closed in their faces? For example ... Salesman Joe routinely writes deals on homes worth over $3 million ... while poor Bill bangs his head against the wall trying to sell $24 cell phones. Lindsay wins awards for moving the most $380,000 Rolls Royce Phantoms during the slow summer months ... while poor Buffy got fired because she couldn't persuade more business owners to try her $79 a month coffee-delivery service. These four salespeople have great personalities, firm handshakes and excellent prospecting and follow-up skills, but the difference in their performance is staggering. This book takes readers on a fascinating tour inside their prospects' minds and teaches 21 powerful techniques of consumer psychology that really work. Plus, dozens of real-life scripts show reacers exactly how to incorporate them into their own sales presentations. --